UNDERSTANDING PERCEPTION OF ORGANIZATIONAL POLITICS IN INDONESIA: EMPLOYEES’ PERCEPTION ON ITS PRACTICE, ANTECEDENTS, AND OUTCOMES - Hafid Fahrian; Mirwan Surya Perdhana (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to investigate the perception of Indonesian Generation Y and Generation Z employee to organizational politics with modern business context in mind. Organizational politics has been popularly viewed as a negative phenomenon within firms, as it often researched using a negatively biased method. The study is catalyzed by the call of past researches to explore deeper the field of organizational politics and to bring a more balanced view of it. Qualitative method, specifically the qualitative phenomenological method, was chosen for this study. The use of phenomenology enabled this research to deliver in-depth understanding for the perception of organizational politics. Informants of this research were drawn from various Indonesian companies, with proportional demographics distribution in term of age cohort and gender. Based on the findings, there are four categories of employee’s political perception, that are Necessary, Necessary to Some Extent, Neutral, and Should be Avoided. This study has also successfully recognized the antecedents of organizational politics, which can lead to the rise political behavior within an organization. Additionally, this study also identified the outcomes of organizational politics that were further classed into two dimensions: individual and organizational impact, with informants’ description encompassed both positive and negative outcomes. Keywords: perception of organizational politics, qualitative study, balanced view on organizational politics.